EFEK DARI BANTUAN SOSIAL LANSIA PEMDA TERHADAP BELANJA KESEHATAN LANSIA MISKIN DI INDONESIA - Niar Afdhal Lythfi Luthfi; Muhammad Hanri (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
This research examines the effect of the local government's elderly social assistance program on out-of-pocket (OOP) health spending for the poor elderly group in Indonesia. The data used is March 2020 Susenas data using counterfactual analysis. Because the requirement to be able to carry out a counterfactual analysis is that the subjects of the study must have the same/balanced characteristics, the data used is limited to the elderly in the bottom 40 percent of the economic group. Moreover, the randomization technique is also carried out using the Propensity Score Matching-Nearest-Neighbors (PSM-NN) method, namely constructing data with similar characteristics into two groups: the group that received treatment and the group that did not receive treatment. The results of this study indicate that the poor elderly group who receive elderly social assistance from the local government has a higher OOP health spending of 28.3 percent compared to the poor elderly group who do not receive assistance. The high spending on OOP was mainly due to increased spending on curative.